Rancang Bangun Aplikasi Penjualan Kardus Pada UD. Stradus Surabaya - Hidayah, Era Norma; Arifin, Mochammad; Erstiawan, Martinus Sony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
ABSTRACT : UD. Stardus Surabaya is one of the distributors of various boxes of food located on the road Simorejo No. 103 Surabaya. These distributors serve only selling wholesale or in large quantities only. Problems on the current business process is the absence of the recording process at the request of customers that are not realized. Distributors also do not know the state of the inventory in real time and does not know when to conduct the procurement process without having to wait for the inventory runs out. Judging from the payment of receivables distributor also has no system for recording receivables tersistem well.Based on the above problems, the researchers use the method of System Development Life Cycle to analyze and evaluate the system to perform system development. Application sales are made useful to keep records of sales activities as the basis for reporting sales activity in real time.Based on the above problem resolution and system testing of the research results, it can be concluded that the application of the sale of cardboard that has been made to produce information in the form of a report which contains information inventory, information requests are not fulfilled, and the information necessary sales receivables UD. Stardus Surarabaya for decision-making by the leadership.